Design and Build of Modification of Fuel Flow as a Tool for Aircraft Refueling in the Hangar of the Aviation Polytechnic of Surabaya - Setijono, Cholik; Sayidul Aziz, Muhammad; Wulansari, Ajeng (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
This plan is motivated by the results of observations regarding the teaching and learning process for Cadets of the Surabaya Aviation Polytechnic, during the run-up and refueling practicum processes. This tool is planned to overcome the inefficiency of the refueling equipment in the Surabaya Aviation Polytechnic hangar, because when cadets do refueling it is not accurate to calculate the fuel that has entered the plane. In making this tool, applying microcontroller technology to a flow meter with a digital display by utilizing Arduino as a fuel flow measurement controller and for a flow meter sensor which functions to calculate the flow of fuel flowing through the tool, the results of the fuel meter measurements are then processed by Arduino which has been Fill in the program then the results are displayed on the LCD display.